2016
DOI: 10.1002/jor.23285
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of meniscal‐ and ACL‐transected mouse knees during controlled tibial compressive loading captured using roentgen stereophotogrammetry

Abstract: Pre-clinical studies of post-traumatic OA have examined the pathways that lead to disease after injury by using surgical models such as the destabilization of the medial meniscus (DMM) and anterior cruciate ligament transection (ACLT). While the morphological, molecular and genetic pathways leading to OA have been examined extensively; the effects of these injuries on joint kinematics, and thus disease progression, have yet to be fully characterized. To this end, we sought to understand the kinematics in the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 53 publications
(129 reference statements)
0
25
0
Order By: Relevance
“…Using a peak load of 9N for 1200 cycles, this model induced controlled instabilities in the knee joint 31 , and recapitulated OA pathology in the cartilage and SCB after 1, 2, and 6 weeks of daily loading in adult C57BL/6 mice 27,28 . A single bout of loading also induced disease initiation and progression, demonstrating that OA pathology in this model can be initiated by cell-mediated processes that are activated by mechanical loading 32 .…”
Section: Introductionmentioning
confidence: 79%
“…Using a peak load of 9N for 1200 cycles, this model induced controlled instabilities in the knee joint 31 , and recapitulated OA pathology in the cartilage and SCB after 1, 2, and 6 weeks of daily loading in adult C57BL/6 mice 27,28 . A single bout of loading also induced disease initiation and progression, demonstrating that OA pathology in this model can be initiated by cell-mediated processes that are activated by mechanical loading 32 .…”
Section: Introductionmentioning
confidence: 79%
“…Another reason may be that the relative short period of time between injury and assessment of cartilage destruction in this model precludes the development of loading induced cartilage damage, at least during the 12-week monitoring period post-injury. Recent mechanical loading studies revealed few kinematic changes in DMM joints (33). Future studies will determine how long Phlpp inhibitor treatment is effective and if inhibitors block the initiation of cartilage damage and/or promote regeneration after the onset of cartilage degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Recent mechanical loading studies revealed few kinematic changes in DMM joints. 33 Future studies will determine how long Phlpp inhibitor treatment is effective and if inhibitors block the initiation of cartilage damage and/or promote regeneration after the onset of cartilage degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the relationship between joint mechanics and the ensuing biological response, a number of in vitro and in vivo models have emerged. In vivo animal models and in vitro tissue explant models have demonstrated that increased joint translation, contact stress, and impact force can lead to cartilage degeneration . In vivo patient‐based studies of joint kinematics and tissue contact have also suggested that changed kinematics during walking can influence changes in joint morphology .…”
Section: Discussionmentioning
confidence: 99%
“…In vivo animal models and in vitro tissue explant models have demonstrated that increased joint translation, contact stress, and impact force can lead to cartilage degeneration. 8,[27][28][29][30] In vivo patient-based studies of joint kinematics and tissue contact have also suggested that changed kinematics during walking can influence changes in joint morphology. 31 Conceptually, a deeper understanding of a patient's joint mechanics and how those mechanics are affected by injury, could be used to assess the risk of joint tissue degeneration after meniscal injury, and hence the need to surgically intervene.…”
Section: Discussionmentioning
confidence: 99%